Semeando conhecimento por meio de um jardim filtrante: proposta de educação ambiental na escola municipal comunitária do Uraim, Paragominas, Pará - PINTO, Alcicléia dos Santos (2022)
The present work was the result of a proposal for the development of Environmental Education through the implementation of a Filtering Garden in the Community School of Uraim, located in the rural area of the city of Paragominas-PA, and brings as a problem the lack of basic sanitation services in the space. municipality's countryside. The methodology adopted a qualitative approach, the research is of an applied nature and, considering the research practice in terms of objectives, it has an exploratory and descriptive character. The first stage of the research consisted of presenting the proposal to the school board. The second stage consisted of implementing and monitoring the operation of the filtering garden, which was built at the research site with adaptations of the methodology used by the Brazilian Agricultural Research Corporation - EMBRAPA - Instrumentation. The total area occupied by the garden was 5.25 m2, which corresponds to a generation of effluents from 3 contributors. The third phase comprised the survey of the school community's perceptions about rural sanitation, where questionnaires were applied to 24 students from the 8th and 9th grades and interviews were carried out with 13 school employees. The analyzes of the collected samples pointed to the effectiveness of the social technology, indicating that the garden was able to act in the removal of the main pollutants present in an effluent, since the parameters evaluated showed significant rates of removal after passing through the filtering garden. As for the survey of the school community's perceptions about basic sanitation, it is perceived that it is still superficial, which may reflect the lack of information, consequently, the passivity in waiting for the public power to solve problems. It is essential that the community understand the importance of rural sanitation, for this, practical proposals such as the filter garden are fundamental for the intertwining of theory with practice, as they provide the construction of new dialogues, aimed at knowing and understanding the environmental difficulties that the community lives and, more than that, to be able to propose solutions.